Teacher’s Reinforcement in English Classroom in MTSS Darul Makmur Sungai Cubadak - Mardhatillah, Elsy (Indonesian Research Journal on Education, 2023)
This research was due to some problems found in MTsS Darul Makmur. First, some students were not motivated in learning. Second, sometime the teacher still uses Indonesian in giving reinforcements. Third, some Students did not care about the teacher's reinforcement. This study aimed to find out the types of reinforcement used by the teacher. Then, to find out the types of reinforcement often and rarely to be usedby the teacher. Then, to find out the reasons the teacher used certain reinforcements. Last, to find out how the teacher understands the reinforcement. This research used a qualitative approach. The design of this research was descriptive because the researcher made a description of the use of reinforcement by theteacher in the English classroom. In this research, the interview and observation sheets were used by the researcher. The researcher found that the type of reinforcement used by the teacher is positive reinforcement and negative reinforcement. First, there were two types of positive reinforcement used by teachers, namely verbal reinforcement and non-verbal reinforcement. The verbal often used by theteacher was a reinforcement in the form of words and reinforcement in the form of phrases. Then, verbal reinforcement in the form of sentences was never done by the teacher in the learning process. While the non-verbal reinforcement often used by the teacher was gestural, activity reinforcement, and proximity reinforcement. Second, the negative reinforcement often used by the teacher was a warning, gesture, and eye contact. Meanwhile, the negative reinforcement rarely used by the teacher was speech volume andpunishment. Third, the reasons teachers reinforce learning are to motivate students and make students feel appreciated and happy while learning.